2020
DOI: 10.1056/nejmoa1912196
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Anifrolumab in Active Systemic Lupus Erythematosus

Abstract: BACKGROUND Anifrolumab, a human monoclonal antibody to type I interferon receptor subunit 1 investigated for the treatment of systemic lupus erythematosus (SLE), did not have a significant effect on the primary end point in a previous phase 3 trial. The current phase 3 trial used a secondary end point from that trial as the primary end point. METHODS We randomly assigned patients in a 1:1 ratio to receive intravenous anifrolumab (300 mg) or placebo every 4 weeks for 48 weeks. The primary end point of this tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
677
0
40

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 857 publications
(793 citation statements)
references
References 26 publications
20
677
0
40
Order By: Relevance
“…Interestingly, the expression and co-expression profiles of BAFF and IL1RN also changed with IFN response status in this longitudinal data (Figure 2E, H). Recently, a phase III clinical trial (TULIP 2, NCT02446899) in SLE patients with a human monoclonal antibody (Anifrolumab) that specifically blocks IFNAR1 (type I interferon receptor subunit 1) was completed 57 . The trial results also suggested that knowing patients' IFN response status before prescribing targeted therapy will be helpful in the clinical setting and in designing further targeted therapies for specific patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression and co-expression profiles of BAFF and IL1RN also changed with IFN response status in this longitudinal data (Figure 2E, H). Recently, a phase III clinical trial (TULIP 2, NCT02446899) in SLE patients with a human monoclonal antibody (Anifrolumab) that specifically blocks IFNAR1 (type I interferon receptor subunit 1) was completed 57 . The trial results also suggested that knowing patients' IFN response status before prescribing targeted therapy will be helpful in the clinical setting and in designing further targeted therapies for specific patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also obtained in patients with a stronger IFN signature. In the TULIP 2 trial the primary endpoint, BICLA (BILAG‐based Combined Lupus Assessment) response rate at week 52 was significantly higher in the anifrolumab group, regardless of IFN signature, and significant differences were also observed in the improvement of the Cutaneous Lupus Erythematosus Disease Area and Severity Index, glucocorticoid‐sparing effect, and SRI‐4 response rate 13 . There was no remarkable difference in the incidence of adverse events between the anifrolumab and placebo groups, except for herpes zoster and bronchitis, which occurred in 7.2% of patients in the anifrolumab group.…”
Section: Biological Therapymentioning
confidence: 99%
“…Zudem konnte erstmals in einer Phase III Studie (TULIP II) die Überlegenheit des Typ-I-Interferonrezeptor Inhibitors Anifrolumab gegenüber Placebo gezeigt werden [19]. Primärer Endpunkt war das Therapieansprechen gemessen mittels BICLA Response.…”
Section: Off-label-therapie Und Substanzen In Der Entwicklungunclassified